Sensores ópticos para quantificação de sulfeto de hidrogênio em matrizes gasosas por espectrometria de floorescênica do UV-visível e espectroscopia de absorção no infravermelho: João Flávio da Silveira Petruci. - - Petruci, Foão Flávio da Silveira [UNESP] (2014)
Among the gaseous pollutants, hydrogen sulfide and its derivatives – also know as Reduced Sulfur Compounds (RSC) – have been attracting attention due their high toxicity, corrosive proprieties and involvement in several environmental issues. For this reason, there are many agencies worldwide that establish limits for the presence of H2S and RSC in several environmental compartments ranging from ppm (μg g-1) to low ppb (ng g-1). In order to enable the monitoring of these compounds in air, analytical methods must provide reliable and accurate results. Optical sensors appear particularly advantageous in terms of equipment cost, simplicity, easiness of operation, and potential for miniaturization. Several chemical compounds with luminescent proprieties have been used as reagent for sulfide detection. However, most of them are based on toxic metals and, furthermore, their synthesis contains many steps and generates toxic residues. In light of this context, a new palladium chelate compound – denominate bis (2-aminobenzoic) palladium (II) – was used to determinate sulfides in aqueous and gaseous samples as described in the first part of this thesis. The compound reacts with sulfides leading to the increase of the fluorescence intensity at 410 nm, when excited at 245 nm. The method was validated and enabled the determination of 0.075 μmol L- 1 and 6.8 ppbv for aqueous sulfide and gaseous H2S, respectively. The second part of this thesis involves the use of infrared spectroscopy coupled to a new generation of hollow waveguides, so-called substrate-integrated hollow waveguides, for the real-time monitoring of H2S in gaseous samples. The determination is based on the instantly and UV-based conversion of H2S to SO2, a very strong IR absorber at 1245 cm-1. The method enables the determination of 3 ppm of H2S.